Sistem Penerimaan Peserta Didik Baru Berbasis Online dan Offline Di Sekolah Menengah Kejuruan - Tri Novia Rosalinda (Faculty of Education Universitas Negeri Malang, 2019)
Abstract: The purpose of this study is to describe; (1) online and offline student admission planning; (2) job description on the structure of the student admission committee; (3) procedures of online and offline student admission; (4) constraints and solution of online and offline student admission; (5) weakness and strength of online and offline student admission; and (6) differences and similarities of online and offline student admission. This study used a qualitative approach with a type of multi-case study. The result of this study are; (1) online and offline student admission is planned; (2) there are student admission committee with task and responbility; (3) online and offline student admission consist of several procedures; (4) student admission has problems and need solution; (5) online and offline student admission has weakness and strenght; (6) there are differences and similarities between online and offline student admission. Abstrak: Tujuan penelitian ini yaitu untuk menderskripsikan; (1) perencanaan PPDB online dan offline; (2) tugas pada struktur kepanitiaan PPDB online dan offline; (3) prosedur PPDB online dan offline; (4) kendala dan solusi PPDB online dan offline; (5) kelemahan dan kelebihan PPDB online dan offline; dan (6) perbedaan dan kesamaan PPDB online dan offline. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi multi kasus. Hasil penelitian ini yaitu; (1) PPDB online dan offline direncanakan; (2) terdapat kepanitiaan PPDB dengan tugas dan tanggung jawab masing-masing; (3) PPDB online dan offline terdiri dari beberapa prosedur pendaftaran; (4) PPDB mengalami kendala dan solusi; (5) PPDB online dan offline memiliki kelemahan dan kelebihan; dan (6) terdapat perbedaan dan kesamaan antara PPDB online dan offline.